Production of medical isotope 68Ge based on a novel chromatography separation technique and assembling of 68Ge/68Ga generator. (February 2023) - Wang, Jieru; Gao, Ruiqin; Cao, Shiwei; Qin, Zhi; Lin, Mu; Huang, Qinggang; Yao, Zeen
Abstract: A double-column chromatography separation technique was involved for isolation of 68 Ge from a bombarded Ga–Ni alloy target. About 185 MBq 68 Ge obtained was used for assembling SnO2 -based 68 Ge/ 68 Ga generator. Approximately 70% of 68 Ga in high radioactivity concentration was eluted from generator with excellent radionuclidic, radiochemical and chemical purity. 68 Ga was quite adequate for radiolabeling with DOTATATE or PSMA-617 with a high labelling efficiency of >92%. The double-column chromatography technique possessed a potential application prospect of 68 Ge/ 68 Ga production, aiding the development of 68 Ga in nuclear medicine. Highlights: A double-column chromatography separation technique was adopted to isolate 68 Ge from an irradiated Ga–Ni alloy target. A SnO2 -based 68 Ge/ 68 Ga generator has been assembled successfully. Th e 68 Ga eluates with excellent purity was labelled with DOTATATE and PSMA-617 with a high efficiency of ＞92%.